Consistency of the Implementation of PERMA Number 5 of 2019 in the Marriage Dispensation Decision: A Child Protection Perspective - Tuti Munawarah (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
Child marriage is still a serious problem in the marriage legal system in Indonesia even though the age limit for marriage has been raised to 19 years through Law Number 16 of 2019. One of the loopholes that allows the practice of child marriage to continue to occur is the existence of a marriage dispensation mechanism that is decided by the court. This study aims to analyze the consistency of the application of PERMA Number 5 of 2019 in the marriage dispensation decision and the legal basis used by judges in considering the application. This study uses normative legal research methods with a legislative approach and a case approach. The results of the study show that judges are generally guided by Law Number 16 of 2019, Law Number 1 of 1974, fiqhiyyah rules, and PERMA Number 5 of 2019 which emphasizes the principles of the best interests of children, justice, utility, and legal certainty as stipulated in Article 2. However, the application of these principles is not completely consistent. In practice, the judge's judgment is often influenced by the maslahah approach, especially in the case of out-of-wedlock pregnancies that are considered urgent reasons. As well as economic factors and visual health assessments. In addition, the Child Protection Law has not been consistently used as a basis for legal considerations. Therefore, it is necessary to strengthen the perspective of child protection in the practice of marriage dispensation justice in order to support the prevention of child marriage more effectively.